Case report: Imaging of adrenal adenomatoid tumors: reports of two cases and review of literature - Wu, Yuanyuan; Hu, Dongliang; Cui, Manman; Liu, Yan; Zhou, Xiuzhi; Zhai, Duchang; Fan, Guohua (Frontiers in Oncology, 2024)
Adenomatoid tumors (ATs) are uncommon, benign tumors of mesothelial origin, most frequently found in the genital tracts of both sexes. Extragenital localization sites, such as adrenal glands, are extremely rare. Since patients with adrenal ATs have no obvious clinical symptoms, imaging examination has become important evidence for diagnosis. Although previous literature noted that the imaging findings of adrenal ATs were nonspecific, no relevant studies have confirmed this. We herein present two novel cases of adrenal ATs, confirmed by immunohistochemistry, and that were initially misdiagnosed as other, more common adrenal tumors based on clinical findings and preoperative imaging. Including our cases, we collected a total of 33 previously reported adrenal ATs and extracted all available imaging information from them, aiming to find some radiological characteristics of this rare tumor. Through the review, we identified some nonspecific imaging features of adrenal ATs; however, the final diagnosis still depends on pathology and immunohistochemistry results.